2014
DOI: 10.1074/jbc.m113.506956
|View full text |Cite
|
Sign up to set email alerts
|

C1q/TNF-related Protein 4 (CTRP4) Is a Unique Secreted Protein with Two Tandem C1q Domains That Functions in the Hypothalamus to Modulate Food Intake and Body Weight

Abstract: Background: CTRP4 is a conserved member of the C1q family of secreted proteins with poorly defined function. Results: CTRP4 acts in the hypothalamus to modulate food intake and body weight by regulating the expression of orexigenic neuropeptide expression. Conclusion: CTRP4 plays a role in food intake regulation. Significance: This study establishes the first known in vivo function of CTRP4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 75 publications
1
65
1
Order By: Relevance
“…Cow HPs are part of the C1q protein family (Kishore et al, 2004) and consist of over 30 members, all of which possess the signature C1q domain at the C-terminus. Several conserved members of this family, such as adiponectin and C1q/TNF-related proteins are involved in modulating food intake (Byerly et al, 2014;Byerly et al, 2013a;Kubota et al, 2007;Qi et al, 2004) and energy metabolism (Berg et al, 2001;Peterson et al, 2012;Peterson et al, 2013;Peterson et al, 2010;Seldin et al, 2012;Wei et al, 2014;Wei et al, 2012b;Wei et al, 2011;Wei et al, 2013;Wong et al, 2009;Wong et al, 2008;Yamauchi et al, 2002). Thus, in mice, the functional homolog of cow HPs may be subsumed by other related C1q family members.…”
Section: Discussionmentioning
confidence: 99%
“…Cow HPs are part of the C1q protein family (Kishore et al, 2004) and consist of over 30 members, all of which possess the signature C1q domain at the C-terminus. Several conserved members of this family, such as adiponectin and C1q/TNF-related proteins are involved in modulating food intake (Byerly et al, 2014;Byerly et al, 2013a;Kubota et al, 2007;Qi et al, 2004) and energy metabolism (Berg et al, 2001;Peterson et al, 2012;Peterson et al, 2013;Peterson et al, 2010;Seldin et al, 2012;Wei et al, 2014;Wei et al, 2012b;Wei et al, 2011;Wei et al, 2013;Wong et al, 2009;Wong et al, 2008;Yamauchi et al, 2002). Thus, in mice, the functional homolog of cow HPs may be subsumed by other related C1q family members.…”
Section: Discussionmentioning
confidence: 99%
“…In 2004, Wong et al characterized a novel family of adipose tissue-derived cytokines, collectively called adipokines, referred to as Complement C 1q T umor necrosis factor- R elated P roteins (CTRPs) (76), like adiponectin and tumor necrosis factor (TNF) these CTRPs all contain a C1q globular domain and are characterized together as the C1q/TNF superfamily (62). To date, this superfamily has been documented to have a wide range and opposing effects on metabolism, food intake, inflammation, tumor metastasis, apoptosis, vascular disorders, ischemic injury, and even sexual reproduction (7, 8, 25, 29, 30, 49, 51, 57, 62, 64, 68, 69, 74-76, 81, 84, 89). The purpose of this review is to carefully summarize the research that has been accomplished on one of these proteins, CTRP3.…”
Section: Introductionmentioning
confidence: 99%
“…Recent functional studies demonstrated important and distinct roles for CTRPs in regulating glucose and/or lipid metabolism in the peripheral tissues (38 -42, 57-60) as well as having a central role in modulating food intake (6,7) and adipocyte differentiation in culture (61). Unlike adiponectin, whose expression is restricted to adipocytes (47), CTRP family members are much more widely expressed (65,66); all are conserved throughout vertebrate evolution (50).…”
mentioning
confidence: 99%